Politik Hukum Cyber Notary dalam Era Digitalisasi 5.0 di Indonesia - Setiawati, Sicilia Firdaus; Samosir, Tetti; Deni, Fitraì (Notarius, 2025)
ABSTRACTThe rise of the digitalization era 5.0 urges legal modernization, including in the notarial field. The Cyber Notary concept emerges as a solution through the application of technology in authentic deed creation. However, Indonesia lacks specific regulations explicitly governing its implementation. This study uses a normative-descriptive approach based on literature review to analyze legal politics and obstacles to Cyber Notary adoption. The findings show that technologies such as AI offer efficiency but require a strong legal foundation to align with notarial principles. Regulatory harmonization, particularly regarding Article 1 point 7 of the UUJN, is crucial to realize a Cyber Notary system that adapts to the digital era.Keywords: Authentic Deed; Notary; Notary's Responsibility; Principle of Care ABSTRAKPerkembangan era digitalisasi 5.0 mendorong modernisasi hukum, termasuk dalam bidang kenotariatan. Konsep Cyber Notary hadir sebagai solusi melalui penerapan teknologi dalam pembuatan akta autentik. Namun, belum ada regulasi khusus di Indonesia yang mengaturnya secara eksplisit. Penelitian ini menggunakan pendekatan normatif-deskriptif berbasis studi kepustakaan untuk menganalisis politik hukum dan hambatan penerapan Cyber Notary. Hasilnya menunjukkan bahwa teknologi seperti AI menawarkan efisiensi, namun memerlukan dasar hukum yang kuat agar selaras dengan prinsip notariat. Harmonisasi regulasi, khususnya terkait Pasal 1 angka 7 UUJN, menjadi urgensi utama untuk mewujudkan Cyber Notary yang adaptif terhadap era digital. Kata Kunci: Akta Otentik; Notaris; Tanggung Jawab Notaris; Prinsip Kehati-hatian